Effects of powder synthesis method on the sinterability of hydroxyapatite - K. L., Aw; Ranna, Tolouei; Singh, Ramesh; Tan, Chou Yong; W,, H. Yeo; H., Kelvin; Iis, Sopyan; Teng, Wan Dung (Trans Tech Publications, Switzerland, 2011)
The sinterability of hydroxyapatite (HA) powder synthesized through a novel wet chemical method (HAp) and a wet mechanochemical method (HAwm) was investigated over a temperature range of 1000oC to 1400oC in terms of phase stability, bulk density, hardness and fracture toughness. The results indicated that the sinterability of HAp powder were significantly better than HAwm powder. Moreover, the XRD traces of HAwm sintered samples showed signs of decomposition into TTCP when sintered at 1300oC and above. Densification of ~98% of theoretical density was attained by HAp compacts at 1100oC while the HAwm compacts exhibited only ~96% of theoretical density even at 1350oC with no significant increase of density at 1400oC. The Vickers hardness of HAp showed increasing trend for temperature range of 1000oC to 1100oC with the compacts attaining HV of ~7 GPa at 1100oC. Subsequently, the hardness decreased with increasing sintering temperature though the value does not dropped below ~5 GPa. Similarly, HAwm compacts showed an increasing trend from 1000oC to 1300oC with the largest HV attained was ~4.57 GPa. Further increased in sintering temperature resulted in the decreased of Vicker’s hardness. Moreover, the HAp samples reached a maximum fracture toughness of ~0.9 MPam1/2 at 1050oC while the HAwm attained maximum KIc of only ~0.7 MPam1/2 at 1300oC.